2020
DOI: 10.1080/15438627.2020.1770760
|View full text |Cite
|
Sign up to set email alerts
|

How manipulation of playing area dimensions in ball possession games constrains physical effort and technical actions in under-11, under-15 and under-23 soccer players

Abstract: How manipulation of playing area dimensions in ball possession games constrains physical effort and technical actions in under-11, under-15 and under-23 soccer players. Research in Sports Medicine, 1-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Studies conducted with athletes older than those in our investigation found HR of 88-89% HR max in 1 × 1 SSG [29,30]. As for the external load, the results are in line with the expectations [8,9,12]. There was an increase in total distance, explosive distance, and maximum sprint with the increase in pitch size.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies conducted with athletes older than those in our investigation found HR of 88-89% HR max in 1 × 1 SSG [29,30]. As for the external load, the results are in line with the expectations [8,9,12]. There was an increase in total distance, explosive distance, and maximum sprint with the increase in pitch size.…”
Section: Discussionsupporting
confidence: 90%
“…In 1 × 1 SSGs, sizes of 5 × 10 m are referred to as small, 10 × 15 m as medium, and 15 × 20 m as large [10,11]. The players' work is influenced by the pitch size [3]; the distance, explosive distance, and maximum sprint raise with increasing playing area [8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, and in opposition to S and L playing areas, it was noticed that in the M playing area, both U11 and U15 felt the SSG more intense when compared with the U23 age-category. Indeed, Nunes et al (2020) reported higher scores of the RPE for U23 players on small playing areas and for U11 players on larger playing areas, with no differences stated for U15 players between areas of play. According to Malina et al (2007) , children feel less effort than adults in training and competitive activities.…”
Section: Discussionmentioning
confidence: 88%
“…As players move further away from each other and as the effective playing space increases, players have more space to move in high-speed running. Other studies highlighted that when playing space increases, the distances covered by the players in different speed zones also increases [26,27]. Nunes et al [26] observed that U-15 and U-23 players performed more sprints in SSCG with a larger playing area.…”
Section: Discussionmentioning
confidence: 98%